Carleman estimate and null controllability of a cascade degenerate parabolic system with general convection terms - Jianing Xu; Chunpeng Wang; Yuanyuan Nie (Electronic Journal of Differential Equations, 2018)
This article shows Carleman estimate and null controllability of a cascade control system governed by the semilinear degenerate parabolic equations with the general convection terms. The semilinear parabolic equations are weakly degenerate on the boundary and the convection terms cannot be controlled by the diffusion terms. We establish the Carleman estimate and the observability inequality for the linear conjugate system, and prove that the control system is null controllable.